A review of reproduction biology and spawning/ nursery grounds of the most important Adriatic commercial fish species in the last two decades - Zorica, Barbara (Array, 2020)
Recently, despite long-term systematic research of the Adriatic Sea ecosystem, the necessity to improve the existing protection of commercially exploited species occurred since the status of many renewable marine stocks were not in good state. In order to realize that review of scientific knowledge gather within the last two decades was required. In this paper emphasis has been placed on all the scientific knowledge concerning the reproductive biology, spawning and nursery grounds of four ecologically and economically important Adriatic fish species – sardine Sardina pilchardus, anchovy Engraulis encrasicolus, European hake Merluccius merluccius, Common pandora, Pagellus erythrinus. Main aim of this review was to establish new scientific platform that in near future should result with better conservation measures that will insure long-term sustainability of exploited marine living resources.